Learning-goals-driven design model: Developing curriculum materials that align with national standards and incorporate project-based pedagogy - Krajcik, Joseph; McNeill, Katherine L; Reiser, Brian J (Science education (Salem, Mass.), 2008)
Reform efforts in science education emphasize the importance of rigorous treatment of science standards and use of innovative pedagogical approaches to make science more meaningful and successful. In this paper, we present a learning-goals-driven design model for developing curriculum materials, which combines national standards and a project-based pedagogical approach. We describe our design model in the context of the Investigating and Questioning our World through Science and Technology (IQWST) project, which is developing a three-year coordinated series of middle grades science curriculum materials. From using this model in the development and enactment of the curriculum, we identified three important characteristics: unpacking national science standards, developing a learning performances approach to specifying learning goals, and aligning learning goals, instructional activities, and assessments. Using a case study of an IQWST unit from initial development through two cycles of enactment, we describe how these three characteristics help guide curriculum design, identify design issues in curriculum enactments, and guide the development of design solutions. The iterative use of the learning-goals-driven design model coupled with the analysis of multiple data sources informed our revision of the curriculum materials, resulting in substantial student learning gains for the targeted science content and scientific inquiry learning goals.